PROTOTIPE KNOWLEDGE MANAGEMENT SYSTEM KOPERASI PADA PERUSAHAAN PERBANKAN: Studi Kasus Koperasi Karyawan Permata Bank - Tuti Handayani (UNIVERSITAS INDRAPRASTA PGRI, 2016)
Permata Bank Employee Cooperative was still unable to well-manage knowledge. Knowledge is one of the crucial aspects for improving the added value of a cooperative. Therefore, a form of system commonly known as Knowledge Management System is highly required in a cooperative. This journal is entitled “Prototype of Knowledge Management System of the Cooperative a Banking Company: A Case Study at PermataBank Employee Cooperative” which was aimed to analyze and apply the benefits of Knowledge Management System in a banking company cooperative, particularly PermataBank Employee Cooperative. In this research, a knowledge management system model was developed for Customer Service by analyzing and designing the system prototype of the model that was developed. The research method used was Tiwana’s framework model, the Organization Knowledge Potentials mapping used Zack’s model, and the knowledge generation used SECI’s model, while the hypothesis testing used Focus Group Discussion (FGD). Focus Group Discussion (FGD) was used for the existing tendency on the perception in a cooperate. This system was not only applied for Customer Service, but also used by other units/departments by developing sharing knowledge at PermataBank Employee Cooperate. This system was expected to be applied at banking companies across Indonesia.